2022
DOI: 10.1007/s10461-022-03624-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Practicalities Influencing Pre-exposure Prophylaxis Adherence Among Men Who Have Sex with Men in England

Abstract: PrEP is highly effective for HIV prevention but requires adequate adherence. In this paper we use the perceptions and practicalities approach (PAPA) to identify factors that influenced PrEP adherence using qualitative data from the PROUD study. From February 2014 to January 2016, we interviewed 41 gay, bisexual and other men-who-have-sex-with-men and one trans woman who were enrolled in the study. We purposively recruited participants for interview based on trial arm allocation, adherence and sexual risk behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Lack of PrEP knowledge was the most studied barrier (Figure 3): it was investigated in 19 of the studies [10, 24, 25, 27, 33–35, 41, 44, 46, 48, 51, 53, 56, 58, 59, 61, 62, 65]. One study found that 44% of survey respondents listed lack of PrEP knowledge as a direct barrier to PrEP use [56].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lack of PrEP knowledge was the most studied barrier (Figure 3): it was investigated in 19 of the studies [10, 24, 25, 27, 33–35, 41, 44, 46, 48, 51, 53, 56, 58, 59, 61, 62, 65]. One study found that 44% of survey respondents listed lack of PrEP knowledge as a direct barrier to PrEP use [56].…”
Section: Resultsmentioning
confidence: 99%
“…Lack of self‐perception of HIV risk was the least studied barrier at the PrEP contemplation step ( n = 12, Figure 3) [10, 24, 34–36, 41, 44, 46, 53, 59, 62, 65]. In Wales, a majority (57%) of those who declined PrEP did so because they did not perceive themselves as at risk of HIV acquisition [10].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations